The contribution of Banu Musa brothers in the self changing fountain - Manshhor, Mohd Romainor; Mirghani, Mohamed Elwathig Saeed (IIUM Press, 2011)
This chapter examines how Banu Musa, innovate and create system that is notthere at that time and documented until it becomes one of the main reference in the world at present.